Effectiveness of after-care-services in the reintegration and supply of labour after incarceration in the prisons: Lagos and Oyo states prison command experience (2011)
Offenders released from correctional institutions are confronted by social, economic and personal challenges that tend to become obstacles to a crime-free lifestyle. Some of these challenges are as a result of the consequences of incarceration and the difficulty of transiting back into the community. It is along this background that this study investigated the effectiveness of After- Care service in the rehabilitation and supply of labour into the economy by ex-offenders in Oyo and Lagos state commands of the Nigerian prison service. The research adopted the descriptive survey research design. A purposive random sampling method was used to select 450 respondents. The main instrument used for the study is a sigle questionnaire with five subsections, each sub section serving as an independent instrument. Data were analyzed using Analysis of Variance (ANOVA). Findings showed that space acquisition and supervision programmes had effect on reintegration and supply of labour into the workplace (F= 76.565; p< 0.05and F=29.630; p< 0.05 respectively), while provision of tools programme does not have significantly effect on reintegration and supply of labour by ex-offender (F= 1.135; p>0.05).It was recommended that the combination of the treatments will solve the problem of recidivism when applied jointly on individual ex-offenders.